PERAN ORANG TUA DALAMPEMBENTUKAN KEPRIBADIAN ANAK: TINJAUAN PSIKOLOGI PERKEMBANGAN ISLAM - Syafi’ah Sukaimi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
Families with any community is a group of social bonds in the domestic family life. The parents, especially the father as the head of the family and the mother as the head of household, are the main actors in the dyeing process of coaching, education, growth and development of children’s personality. Ideal personality of children relies heavily on the efforts of both parents as early as possible so that children are able to understand a wide range of recognition, social experience through guidance, exercises and education, particularly through the development process of religious well.With morale through spiritual, is a guarantee for the kids there will be hope of an Islamic character or personality of noble character.